Analyses and recommendations for legal regimes of children's right to safe drinking water (2017)
Studies which discussed the groundwater quality and, management have been duly published. However, little or no attention is paid to on how policy and standard affect the children's access to portable water in Nigerian hydrogeological literature. Considering contamination, depletion and unequal distribution of water, about 1.8 million children die of diarrhea and other water-borne diseases every year. Unfortunately, water has not been clearly stated as a human right though, it sits at the very essence of the right to life and other fundamental human rights. The right to water needs be recognized in a wide range of international documents, including treaties declarations and other standards. The textual study of literature, and legislation to appropriate lawful endorsement of water to satisfy the needs of the children population were made use of in this study. The ma r focus is on children's entitlement to water facilities under international laws. It also incorporates broader water- related rights in a more holistic interpretation of existing international human rights law. Access to safe water and basic sanitation is recommended to be a legal entitlement, rather than a commodity or service provided on a charitable basis. In addition, hydrogeological contribution for technical support of legal regimes will better provide children with portable water supply. The right to water should clearly fall within the category of fundamental human rights essential for securing an adequate standard of living for children, particularly as one of the most essential conditions for survival